DEVELOPMENT OF SARCOSPORIDIUM SARCOCYSTIS TENELLA RAILLIET, 1886 IN FELINE INTERNAL ORANS (Scientific journal of the Fergana State University, 2023)
The article presents the results of an experiment conducted in 1886 to determine how Sarcocystis tenella Railliet, which lives in all the internal organs of cats, develops in the cat's body.